Chemical and Physical Properties of Meadowfoam Seed Oil and Extra Virgin Olive Oil: Focus on Vibrational Spectroscopy - Zielińska, Aleksandra; Wójcicki, Krzysztof; Klensporf-Pawlik, Dorota; Dias-Ferreira, João; Lucarini, Massimo; Durazzo, Alessandra; Lucariello, Giuseppe; Capasso, Raffaele; Santini, Antonello; Souto, Eliana B.; Nowak, Izabela (Journal of Spectroscopy, 2020)
In food industry, vegetable oils are commonly used as functional ingredients. Cold pressed oils containing fatty acids show a variety of chemical properties, which are mainly dependent on the saturation of fatty acids. In this study, we have analyzed meadowfoam seed oil (MSO), obtained from seeds of Limnanthes alba, and extra virgin olive oil (EVO). Firstly, the fatty acids composition, denoted as Cox value, was determined for the oils that are considered as the most stable. The Cox value for MSO reached 0.032, while that for EVO was 1.780. We have also determined the content of fatty acids in both of the oils using gas chromatography, while the use of mid-infrared (MIR) and near-infrared (NIR) spectroscopy allowed us to assign bands corresponding to the vibrations present in the tested functional groups. Significant differences in the shape and intensity of some bands were observed due to different content of unsaturated fatty acids. Vibrational spectroscopy methods confirmed the presence of long chain fatty acids in MSO.